Impact of cluster building in labor intensive industries on regional economy (Western Romania) - Claudia POPESCU (Transylvanian Review of Administrative Sciences, 2018)
Starting with the mid-1990s, the Western Romania footwear cluster has emerged and grown attaining a critical mass of producers and suppliers. Statistical data analysis based on Location Quotient (LQ) supports the relative concentration of firms and jobs in the footwear cluster as compared to the rest of the regions. The higher LQ values of firms are positively correlated with high levels of entrepreneurship and qualified and diversified labor pool, whereas the high LQ of footwear employment shows the large scale production at region-industry level. Better performance of the firms in the cluster is revealed by much higher averages of turnover, size and profit as compared to the national average. Along the process of cluster building, the composition of the firms has turned hierarchical by functions, and diverse by size and production capabilities. Therefore, the cluster has gradually made the transition from a low-tech, labor intensive manufacturing to a local production system based on skills, knowledge and end-of-line activities. The findings of the paper reveal the impact of the cluster building on the regional economy in terms of specialization, competitiveness, integration into the global supply chain, and spatial pattern. Finally, the analysis will provide insights into the relations between the footwear cluster, regional development and policy design.